Sauropus androgynus Effect on Periodontal Tissue Inflammatory Cells with Orthodontic-Separators - Hillda Herawati; Euis Reni Yuslianti; Ainan Salsabila (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2023)
Orthodontic treatment aims to correct the improper arrangement of teeth. Tooth movement caused by orthodontic treatment causes tension and compression areas in the tooth's supporting tissues. The periodontal ligament will respond to this stimulus by triggering the inflammatory process. Flavonoids in Sauropus androgynus act as anti-inflammatories by inhibiting lipoxygenase and cyclooxygenase. This experimental research was conducted on 32 guinea pigs, which were grouped into 2 groups: the control group had a rubber separator applied for 14 days, and the experimental group had a rubber separator applied also given ethanol extract of Sauropus androgynus 78.3 mg/kg BW. Samples were taken on days 0, 3, 7 and 14 and statistically analyzed using an independent T-test and Mann-Whitney test. The results showed that the ethanol extract of Sauropus androgynus affected the number of inflammatory cells. Based on statistical results, there were significant differences between the control group and the treatment group in neutrophil cells (p=0.000), eosinophils (p=0.000), lymphocytes (p=0.002), and monocytes (p=0.000). In contrast to macrophage cells, statistical results showed no significant difference between the control and experimental groups with p=0.064. The observed effects of the ethanol extract of Sauropus androgynus on periodontal ligament inflammatory cells (neutrophils, eosinophils, lymphocytes, and monocytes) suggested its potential as an anti-inflammatory agent.